Unpacking the value of traditional African vegetables for food and nutrition security - Mwadzingeni, L.; Afari-Sefa, Victor; Shimelis, Hussein; N'Danikou,S.; Figlan, S.; Depenbusch, L.; Shayanowako, A.I.T.; Chagomoka, T.; Mushayi, M.; Schreinemachers, P.; Derera, J. (Springer, 2021)
There is a need for agriculture in sub-Saharan Africa to diversify into more nutrient-rich crops to meet the subcontinent’snutritional needs in terms of micronutrients and reduce health risks related to high and rising rates of overweight/obesity.Many traditional African vegetables (TAVs) are nutrient-dense and have much potential to reduce malnutrition. These vegetablescan also provide sustainable incomes to rural, urban and peri-urban farming communities. In addition to their high economicvalues and health benefits, most TAVs are amenable to be grown under low input conditions and even organically. However,TAVs are under-researched and underutilized across the vegetable value chain. This paper provides a detailed account of thevalue of TAVs, focusing on their importance, research and development progress, and future needs. To exploit the potential ofTAVs, there is need for a more concerted research and development efforts including effective characterization of the nutritionand genetic profiles; enhancing adaptability and yield gains; and capacity development in value addition, postharvest handling,processing, marketing, and seed system development. Success in these areas depends on effective collaborations among nationaland international partners including the private seed sector, and government and non-governmental organizations working in theareas of agriculture, nutrition and health.